Gut microbiome in neuropsychiatric disorders - Diana Marcela MEJÍA-GRANADOS; Benjamín VILLASANA-SALAZAR; Ana Carolina COAN; Liara RIZZI; Marcio Luiz Figueredo BALTHAZAR; Alexandre Barcia de GODOI; Amanda Morato do CANTO; Douglas Cescon da ROSA; Lucas Scárdua SILVA; Rafaella do Rosario TACLA; Alfredo DAMASCENO; Amanda DONATTI; et al. (Arquivos de Neuro-Psiquiatria)
ABSTRACT Background: Neuropsychiatric disorders are a significant cause of death and disability worldwide. The mechanisms underlying these disorders include a constellation of structural, infectious, immunological, metabolic, and genetic etiologies. Advances in next-generation sequencing techniques have demonstrated that the composition of the enteric microbiome is dynamic and plays a pivotal role in host homeostasis and several diseases. The enteric microbiome acts as a key mediator in neuronal signaling via metabolic, neuroimmune, and neuroendocrine pathways. Objective: In this review, we aim to present and discuss the most current knowledge regarding the putative influence of the gut microbiome in neuropsychiatric disorders. Methods: We examined some of the preclinical and clinical evidence and therapeutic strategies associated with the manipulation of the gut microbiome. Results: targeted taxa were described and grouped from major studies to each disease. Conclusions: Understanding the complexity of these ecological interactions and their association with susceptibility and progression of acute and chronic disorders could lead to novel diagnostic biomarkers based on molecular targets. Moreover, research on the microbiome can also improve some emerging treatment choices, such as fecal transplantation, personalized probiotics, and dietary interventions, which could be used to reduce the impact of specific neuropsychiatric disorders. We expect that this knowledge will help physicians caring for patients with neuropsychiatric disorders.